Solving the Power Flow Problem in Transmission Networks Using Nonlinear complex-domain Modeling Via Julia Software - Montoya, Oscar Danilo; Rivas-Trujillo, Edwin; Gil-González, Walter (Ingeniería, 2024)
Solving the power flow problem for transmission grids is crucial for ensuring the reliable and efficient operation of electrical power systems. Power flow analysis allows engineers to determine the voltage, current, and power flow of a network, which is essential for maintaining system stability and avoiding overloads.